Pertimbangan Hakim untuk Dilakukan Rehabilitasi Terhadap Pelaku Tindak Pidana Penyalahgunaan Narkotika Golongan I (Studi Putusan No. 290/Pid.Sus/2016/PN.Gns) - Zainab Ompu Jainah (KEADILAN PROGRESIF, 2017)
Narcotics abuse is unlawful and unlawful use done not for the purpose of treatment, but because it wants to enjoy its influence, in excess, irregular, and lasts long enough to cause physical, mental and social health problems. The problem in this research is how the judge's consideration in breaking the rehabilitation of the perpetrators of the criminal act of drug abuse class I against Decision No. 290 / Pid.Sus / 2016 / PN.Gns. Normative juridical approach and empirical, data analysis used is qualitative. Based on the research results it is known that the judge's consideration stated that the defendant can be classified as a narcotics addict because the defendant's actions have been done since 2000 up to now and connected with the purpose of use to obtain pleasure, euphoria or add energy which is done continuously and produce securities Then the defendant can be in a state of narcotic dependence. As the recommendation is expected if law enforcement officers from the Police, Attorney and Court take the decision of rehabilitation can guarantee the defendant will not repeat the action again for that there must be coordination with the hospital where the Narcotics Abuse Group I is done rehabilitation.